1997
DOI: 10.1097/00005392-199707000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Epirubicin Versus Doxorubicin for Superficial Bladder Tumors (Stages pTa and pT1): a Randomized Prospective Study

Abstract: This study demonstrates that epirubicin has better efficacy and lower toxicity than doxorubicin when used as an intravesical agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Other studies did not find a difference in efficacy between different drug concentrations [31][32][33][34]36]. Weekly instillations during 5 mo appear to be as effective as long-term instillations during 3 yr, which were given less frequently during the initial 5-mo period [26,27].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Other studies did not find a difference in efficacy between different drug concentrations [31][32][33][34]36]. Weekly instillations during 5 mo appear to be as effective as long-term instillations during 3 yr, which were given less frequently during the initial 5-mo period [26,27].…”
Section: Discussionmentioning
confidence: 85%
“…No difference in efficacy was found between the two doses for either 4 wk or 2 yr of treatment. When 18 instillations of epirubicin were given within 1 yr, there was no difference between 50 mg/50 ml (900 mg) and 80 mg/50 ml (1440 mg) in the percentage who had recurrence, 25.0% versus 17.6%, respectively [33]. Likewise, there was no difference in efficacy in a trial comparing 30 mg/30 ml to 60 mg/60 ml of thiotepa where instillations were given every 4 wk for a maximum of 2 yr [34].…”
Section: Two Years Of Chemotherapy-two Trials Compared Weekly Instillmentioning
confidence: 90%
See 1 more Smart Citation
“…17 Multivariate analysis from other studies has identified several risk factors for poor prognosis for Stage pTa-pT1 bladder cancer, including stage, grade, tumor multiplicity, tumor size, association with CIS, previous recurrence, and results of the 3-month cystoscopy. [2][3][4][5][6][7][8][9][10][11] These studies have also shown that lamina propria invasion is 1 of the most important prognostic indicators. All these studies have presented global information on patients with non-muscle invasive bladder cancer: both Ta and T1 tumors were included, and the tumor grades ranged from 1 to 3.…”
Section: Commentmentioning
confidence: 99%
“…1 Much research on Stage T1 tumors of the bladder has been devoted to the identification of risk factors for recurrence and progression. [2][3][4][5][6][7][8][9][10][11] Heney 12 stated that, "in T1 tumors the individual course is difficult to predict, especially in grade 2 (WHO [World Health Organization] 1973) disease. "…”
mentioning
confidence: 99%